RANCANG BANGUN MEDIA DESAIN KATALOG PENUNJANG INFORMASI DAN PROMOSI PT GLOBAL BANGUN MANDIRI - Wahyu Hidayat; Andriansyah Andriansyah; Reni Wulandari (UNIVERSITAS RAHARJA, 2018)
The development of communication media and information today due to the many information needed by everyone, so the information makers continue to be encouraged to make changes to follow the demands of the times. Where many parties are involved, either directly related to the delivery process, or the acceptance of such information. This information delivery model and system will determine whether the process is working properly. One form of media that is considered effective and can be used as a support in the program information and promotion is through a visual communication or through a catalog. Design Catalog is a way an institution or company commonly used as a sign of identity in doing a good communication and within the internal scope of the company and with colleagues, business partners, or other relevant parties. This study aims to apply the concept of Catalog Catalog media to provide information and more effective promotion of the company's products. Currently PT Global Bangun Mandiri is a company engaged in the field of property where many companies are moving companies together and certainly a competitor. To obtain the necessary data during the research, the author uses several methodologies, among others: problem analysis methods, data collection methods (observation, interview, literature study), design analysis methods, and design concepts. The final result of this research is in the form of Design of Catalog Form media which is expected to deliver effective information and promotion message made with interesting layout with a more visual appearance and easy to understand.